Is Sub-Saharan Africa on a Genuinely Sustainable Development Path? Evidence Using Panel Data. (November 2017) - Bissoon, Ourvashi
Although resource rich, sub-Saharan Africa (SSA) has in general been characterised by poor economic performance and widespread poverty. The region is, however, now poised to enjoy high levels of growth and is increasingly attracting foreign direct investment (FDI). However, it is important to determine the sustainability of this development path. Given the lack of research on sustainability in the context of SSA, this study attempts to bridge this gap. A capital approach is adopted using the genuine savings (GS) rate computed by the World Bank, a measure of weak sustainability. GS endeavour to assess the sustainability path of countries, based on how 'well' they manage their total capital stock through the difference between consumption in natural capital and counter-balancing investments in other forms of man-made capital, namely physical and human. Since GS is based on the assumption of perfect resource substitutability, it can be taken as a limit value of sustainability whereby a country experiencing a positive value of GS is deemed to be weakly sustainable. This article thus aims to investigate whether SSA is on a sustainable development path and the factors affecting GS for this sample of countries. This study looks at a panel data set of 30 SSA countries over a period of 35 years. The fixed, random as well as dynamic effects are taken into account using System-GMM. In particular, improving institutional quality in the countries considered in the sample could directly and significantly improve their weak sustainability. JEL Classification: O11, Q01, B22, C23